+0  
 
0
161
4
avatar+102 

https://prnt.sc/hxrawm

 

https://prnt.sc/hxrb69

 

https://prnt.sc/hxrb82

 

https://prnt.sc/hxrb82

 

https://prnt.sc/hxrc2c

 

https://prnt.sc/hxrc3r part 1

https://prnt.sc/hxrcqz part 2

 

https://prnt.sc/hxrdwa part 1

https://prnt.sc/hxrdjk part 2

 

https://prnt.sc/hxrei9

 

https://prnt.sc/hxrekx

 

https://prnt.sc/hxreno part 1

https://prnt.sc/hxrf99 part 2

 

https://prnt.sc/hxrfod

 

https://prnt.sc/hxrfu8

Severoth  Jan 8, 2018
 #1
avatar+87334 
+2

Here's a few

 

First one :

 

AC / BC  = DF  = EF

 

12 / 18   =  10 / EF

 

2 / 3   =  10   /  EF      and we can write

 

3/2  =  EF / 10           multiply both sides by 10

 

10 (3/2)  = EF  =  15

 

 

Second one :

 

SSS  Similarity Theorem

 

Third one  :

 

x / 42  =  6  /36

 

x / 42   =  1 / 6

 

6x  =  42

 

x  =  7 cm

 

 

Fourth one :

 

Proportional

 

c2

 

Segment Addition Postulate

 

 

 

Fifth one....1st part

 

Corresponding Angles Postulate

 

2nd part

 

 ΔACE   similar to  Δ BCD

 

Segment Addition Postulate

 

 

Sixth one  :

 

Definition of Angle Bisector

 

Angle ADB  congruent to  Angle CDF

 

Substitution Property

 

 

Seventh One :

 

DB  / BA   =  CE  / AC

 

6  /  15  =  CE  /  25

 

2 / 5   =  CE  / 25     multiply through by 25

 

(2 / 5) (25)  =  CE   =  10

 

 

Eighth one :

 

CB  / CA    =  BD   / AD

 

7.5 / 4   =  BD   / 3        mutiply through by 3

 

(3/4) (7.5)   =  BD   =  x  =    5.625

 

 

 

 

cool cool cool

CPhill  Jan 8, 2018
edited by CPhill  Jan 8, 2018
 #4
avatar+102 
0

Thanks so much!

Severoth  Jan 8, 2018
 #2
avatar+87334 
+2

Ninth one :

 

Definition of Bisector

 

Alternate Interior Angles Theorem

 

Substitution Property

 

 

Tenth one  :

 

[ x + 8 ]  / 10  =  [2x + 5 ] / 14      cross-multiply

 

14 [ x + 8 ]  =  10  [ 2x - 5 ]

 

14x + 112  =  20x - 50         add 50 to both sides, subtract 14x from both sides

 

162  =  6x              divide both sides by 6

 

27  =  x   

 

 

Last one :

 

Base  =  √ [ 18^2   - 9^2 ]   =  9√ [ 2^2 - 1^2 ]  =  9√3   ≈ 15.6 in

 

 

cool cool cool

CPhill  Jan 8, 2018
 #3
avatar+102 
+1

thank  you so much!

Severoth  Jan 8, 2018

8 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.